Corporate social responsibility: A strategy for social and territorial sustainability - Letizia Carrera (International Journal of Corporate Social Responsibility (JCSR), 2022)
Globalization and financial processes have progressively generated an intense and problematic phenomenon of dis- connection between companies and their territories. Breaking of the spatial link has often led to the breaking of the social bond and the rupture of territorial cohesion. In order to counteract this process of progressive lack of solidarity and social trust between companies and territorial communities, a very important role can be played by Corporate Social Responsibility. From few decades the European and the national reflection was focused on "Corporate Social Responsibility" considered a fundament strategy able to activate the (re) construction of new forms of solidarity and to create favorable conditions for social and economic sustainable growth, restoring continuity between activities and long-term effects connected to them. In this perspec- tive, the corporate territorial welfare is its empirical expression, and a strategic tool to achieve the goal of counteract social and geographical peripherality to guarantee a polycentric and sustainable development of territories and high- est level of quality of life of local communities. To grasp this new type of relationship that companies can establish with "their" territories starting from their choices of welfare, different models of corporate welfare introduced in some companies in Puglia have been analyzed. A spe- cific attention has been dedicated to the particular form of corporate welfare extended to the territory and therefore to territorial stakeholders. These actions, when present, go well beyond the most classic attention to employees, and can be considered opportunities to give shape or rebuild the most direct link with the territories. In order to inves- tigate the corporates' welfare choices, we have used a qualitative methodology interviewing the human resources managers of several Apulian companies and asking them about welfare choices. From the analysis carried out it has been possible to define a typology of enterprises in relation to the adopted model of welfare. The objective that we intend to pursue with this ongoing research is to define a kind of open catalogue of good prac- tices that can facilitate the choices of companies to adhere to innovative forms of corporate and territorial welfare.
Keywords: 650; Communities quality of life; Corporate social responsibility; Solidarity; Sustainability; Territories